A new species and four new records of Stirellus Osborn & Ball (Hemiptera: Cicadellidae: Deltocephalinae: Stenometopiini) from Pakistan with a revised key to species - Shah, Bismillah; Naveed, Hassan; Duan, Yani (Zootaxa, 2020)
The leafhopper genus Stirellus is reviewed from Pakistan with the description and illustrations of a new species Stirellus pakhtunensis Shah & Duan sp. n. and four new records Stirellus capitatus n. rec., Stirellus indrus n. rec., Stirellus rotundus n. rec., Stirellus rubrolineatus n. rec. A checklist and key for the known species of Stirellus from Pakistan are also given.